2022
DOI: 10.3389/fimmu.2022.938075
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA-Seq reveals changes in immune landscape in post-traumatic osteoarthritis

Abstract: Osteoarthritis (OA) is the most common joint disease, affecting over 300 million people world-wide. Accumulating evidence attests to the important roles of the immune system in OA pathogenesis. Understanding the role of various immune cells in joint degeneration or joint repair after injury is vital for improving therapeutic strategies for treating OA. Post-traumatic osteoarthritis (PTOA) develops in ~50% of individuals who have experienced an articular trauma like an anterior cruciate ligament (ACL) rupture. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 97 publications
1
21
0
Order By: Relevance
“…IGF-1 is known to have chondroprotective effects, such as stimulating neocartilage formation, promoting cell survival, and enhancing the integrity of ECM [ 44 , 45 ]. A recent posttraumatic murine model has shown that subpopulations of resident knee joint macrophages constitute a significant source of this IGF1 expression, and chondrocytes (expectedly) have high expression of IGF1R in the 3–7 days following compressive ACL rupture [ 46 ]. In the current porcine study, expression of IGF1 was elevated at 7 days, and it remained elevated at 4 and 52 weeks following ACL transection—suggesting that cartilage may work to maintain a chondroprotective effort even a year after injury.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 is known to have chondroprotective effects, such as stimulating neocartilage formation, promoting cell survival, and enhancing the integrity of ECM [ 44 , 45 ]. A recent posttraumatic murine model has shown that subpopulations of resident knee joint macrophages constitute a significant source of this IGF1 expression, and chondrocytes (expectedly) have high expression of IGF1R in the 3–7 days following compressive ACL rupture [ 46 ]. In the current porcine study, expression of IGF1 was elevated at 7 days, and it remained elevated at 4 and 52 weeks following ACL transection—suggesting that cartilage may work to maintain a chondroprotective effort even a year after injury.…”
Section: Discussionmentioning
confidence: 99%
“…Among these studies in different tissues, immune cells were between 5 and 45% of all cells. A recent study using digested mouse knees found that 78.4%–70.4% of cells were Cd-45 positive using flow cytometry, with neutrophils composing the majority of those cells [ 34 ]. Cd-45 positive high immune cell component of our whole joint samples may be explained by the presence of bone marrow, which is a primary hematopoietic organ.…”
Section: Discussionmentioning
confidence: 99%
“…This manuscript presents one example where integration of mouse data from this study and human data from the pain study above [24 ▪ ] will be powerful. Sebastian et al [26] used a similar posttraumatic model to characterize immune cells in the injured mouse knee joint. While they identified a large number of different immune cells in the knee, macrophages and monocytes underwent the most changes post injury.…”
Section: Single Cell Analysesmentioning
confidence: 99%